Media (in)visibility of translators and interpreters during the war in Ukraine: Analysis of El Mundo’s publications - Cedillo Corrochano, Carmen Mª (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This research evaluates the media treatment given to translators and interpreters during the war in Ukraine, with the main objective of finding out the coverage they have received in El Mundo, one of the most widely read newspapers in Spain. To this end, its publications from 24 February to 14 April 2022 were analysed quanti-qualitatively. The resulting corpus yielded a total of 49 texts/60,000 words and revealed the media invisibility of these professionals in the Spanish press, despite their important role in conflict situations.